Orientation selectivity in infancy: behavioural evidence for temporal sensitivity. - Hood, B; Atkinson, J; Braddick, O; Wattam-Bell, J (1992)
One-month-old infants were tested with a habituation-recovery paradigm to determine whether they could discriminate phase-shifting grating patterns that switched between two orientations, three or eight times a second, from grating patterns that only shifted in phase. The infants were found to discriminate patterns switching orientation at the lower temporal rate of 3 reversals s-1, but not 8 reversals s-1. This finding supports the idea that orientation-selective mechanisms improve in their temporal sensitivity during early infancy. Where they can be compared, the results from behavioural and electrophysiological studies agree as to the course of this development.